2018
DOI: 10.1177/0956797618795679
|View full text |Cite|
|
Sign up to set email alerts
|

Mind the Depth: Visual Perception of Shapes Is Better in Peripersonal Space

Abstract: Closer objects are invariably perceived as bigger than farther ones and are therefore easier to detect and discriminate. This is so deeply grounded in our daily experience that no question has been raised as to whether the advantage for near objects depends on other features (e.g., depth itself). In a series of five experiments (N = 114), we exploited immersive virtual environments and visual illusions (i.e., Ponzo) to probe humans’ perceptual abilities in depth and, specifically, in the space closely surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Since certain critical stimuli in evolutionary terms, such as threats, tend to appear in the LoVF (Isbell, 2006), stimuli appearing at this hemifield should present certain perceptual advantage (in terms of detection and recognition). Indeed, several studies confirm this LoVF advantage in target detection tasks (e.g., Blini et al, 2018;Losier & Clane, 2004). Other studies exploring several visual attributes show the LoVF advantage is limited to parameters such as of motion, contrast and hue, whereas others, such as distance/ depth, would be better perceived for UFV stimuli (e.g., Levine & McAnany, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…Since certain critical stimuli in evolutionary terms, such as threats, tend to appear in the LoVF (Isbell, 2006), stimuli appearing at this hemifield should present certain perceptual advantage (in terms of detection and recognition). Indeed, several studies confirm this LoVF advantage in target detection tasks (e.g., Blini et al, 2018;Losier & Clane, 2004). Other studies exploring several visual attributes show the LoVF advantage is limited to parameters such as of motion, contrast and hue, whereas others, such as distance/ depth, would be better perceived for UFV stimuli (e.g., Levine & McAnany, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…2002 ), and hence, the fact that, when paired with tactile stimuli, this component is moderated by visuo-tactile distance implies that visual perception itself may be different within and outside the PPS. Indeed, initial studies in this domain have suggested that shape discrimination is better within the PPS—even after accounting for relative size ( Blini et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above there is no general consensus about the role of depth in attentional processing. Yet, several studies indicate that there is an egocentric attentional gradient through space that implies prioritization of stimuli in near compared to far depth planes (Andersen & Kramer, 1993;Arnott & Shedden, 2000;Blini et al, 2018;Chen, Weidner, Vossel, Weiss, & Fink, 2012;Downing & Pinker, 1985;Finlayson & Grove, 2015;Plewan & Rinkenauer, 2016Wang, Liu, Chen, & Zhang, 2016). In a recent study, Finlayson and Grove (2015) presented a visual search task across up to four depth planes.…”
Section: Introductionmentioning
confidence: 99%